Insights from antiaging-related X discussions: A six-year #Longevity hashtag analysis study - Joanna Bensz; Dariusz Sołdacki; Zilin Ma; Farhan Bin Matin; Maima Matin; Atanas G. Atanasov (Current Research in Biotechnology)
As social media platforms continue to play an increasingly significant role in shaping public discourse and disseminating scientific information, understanding how longevity and aging-related topics are discussed online has become crucial for researchers and healthcare professionals. This study investigates the global discourse on longevity and aging through the analysis of the hashtag #Longevity on the social media platform X (formerly Twitter) over a six-year period from August 1, 2018, to August 1, 2024. A total of 382 032 posts were shared by 109 935 users across 200 countries. The analysis focused on revealing key themes, geographical distribution, sentiment analysis, and the most frequently mentioned supplements and drugs related to longevity. The results show a high level of engagement with the hashtag, primarily driven by users from the United States, followed by the United Kingdom and Canada. Sentiment analysis revealed predominantly positive attitudes towards longevity-related topics, with a slight but statistically significant (p < 0.0001) decline during and after the COVID-19 pandemic. The study identified nicotinamide mononucleotide, rapamycin, and green tea as the most frequently mentioned supplements or drugs in longevity discussions. Notably, there was a significant increase in discussions about niacin derivatives, particularly nicotinamide mononucleotide, during and after the pandemic period. This study highlights the importance of social media as a tool for gauging public interest and sentiment towards scientific topics like longevity, providing valuable insights for researchers, healthcare professionals, and policymakers to enhance science communication and public engagement.